SISTEM KEAMANAN BAHAYA JARAK JAUH - Mudrika (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The development of technology, especially those using smartphones with the Android operating system, is something that cannot be avoided in this life, because technological progress will run in accordance with scientific progress. Every innovation is created to provide positive benefits for human life. With control using a smartphone and a process using a microcontroller, a tool is made to notify the safety of danger on a smartphone. Buzzer and LED as an indicator and notification or notification on the smartphone there is danger or not with communication using Bluetooth HC-05, when the distance sensor gets detection of an object or not using the Ultrasonic sensor HC SR04. With this tool can find out whether there is danger or not from a distance where this tool is activated, such as at home, in buildings or in factories.